Liquidty Freezes and Market Runs; Evidencefrom the Panic of 1907 - Thomas Paul Gehrig; Caroline Fohlin; Marlene Haas (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Using a new daily dataset for all stocks traded on the New York Stock Exchange, we study the evolution of information asymmetry during runs on financial institutions and the subsequent liquidity freeze of October 1907 - one of the severest financial crises of the 20th century. We find that increased informational risk and resulting runs on financial institutions led to a freeze in short-term money markets, which forced liquidation of stock positions, and drained liquidity from the stock market: spreads increased from 0.5% to 3% during the crisis episode. This liquidity freeze was primarily driven by fears of informed trading and was most intense for the mining sector. In addition to wider spreads and tight money markets, freezing liquidity manifests itself in fading trading volume and increased price sensitivity to changes in trading volume. Importantly, short-term liquidity measures did not have a long-lasting soothing effect on trading volume, but only on prices. We go on to show that rising illiquidity is associated with lower asset prices. Thus, our findings demonstrate how opaque markets can easily transmit an idiosyncratic rumor into a long-lasting, market-wide crisis. They demonstrate the usefulness of illiquidity measures to alert market participants to pendings market runs.
Keywords: G14; D84; E44; 330